2019
DOI: 10.18203/2349-2902.isj20195097
|View full text |Cite
|
Sign up to set email alerts
|

Prospective trial comparing open approach of Lichtenstein tension-free mesh with laparoscopic transabdominal preperitoneal approach for repair of inguinal hernia: tertiary center experience

Abstract: Background: The introduction of various open mesh and laparoscopic techniques has increased the interest in inguinal hernia surgery. But still controversy persists about the most effective inguinal hernia repair. The aim of this study was to compare the results of open Lichtenstein tension-free mesh technique and laparoscopic transabdominal preperitoneal (TAPP) repair for inguinal hernia.Methods: We considered 55 patients were enrolled between. Patients were divided into two groups, group A had open mesh repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Helmy et al reported that in patients with bilateral hernia managed laparoscopically less analgesia required (mean of VAS score 4.29) while in open procedure they needed more analgesia (mean of VAS score 6.74), it did not differ between both groups as regard unilateral hernias. 31 While Koju et al reported a significant difference in pain score with low pain score in TAPP group was seen to be (2.00±0.63 versus 3.90±0.73, p<0.001). 33 Also Garg et al reported that at 0, 12, 24 and 72 hours postoperatively, LH patients described significantly less pain than the open group (p<0.05).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Helmy et al reported that in patients with bilateral hernia managed laparoscopically less analgesia required (mean of VAS score 4.29) while in open procedure they needed more analgesia (mean of VAS score 6.74), it did not differ between both groups as regard unilateral hernias. 31 While Koju et al reported a significant difference in pain score with low pain score in TAPP group was seen to be (2.00±0.63 versus 3.90±0.73, p<0.001). 33 Also Garg et al reported that at 0, 12, 24 and 72 hours postoperatively, LH patients described significantly less pain than the open group (p<0.05).…”
Section: Discussionmentioning
confidence: 88%
“…Helmy et al found that there was great difference between mean of time needed to regain activity between both groups, it was 26.3 in Group A (open) while in Group B (TAPP) was 5.73. 31 Koju et al found that the average hospital stay in TAPP and Lichtenstein's group was 2.33±0.62 and 2.96±0.20; p<0.001, respectively also, there was early return to normal work in TAPP group than in Lichtenstein's group (13.39±0.60 versus 17.88±0.87 days, p<0.001). 33…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation